Do agronomic approaches aligned to regenerative agriculture improve the micronutrient concentrations of edible portions of crops? A scoping review of evidence - Manzeke-Kangara, Muneta Grace; Joy, Edward J. M.; Lark, R. Murray; Redfern, Sally; Eilander, Ans; Broadley, Martin R. (Frontiers in Nutrition, 2023)
Regenerative Agriculture (RA) is used to describe nature-based agronomic approaches that aim to build soil health and crop resilience, minimize negative environmental outcomes, and improve farmer livelihoods however, there remains no universally accepted definition of the term. A benefit that is increasingly attributed to crops grown under RA practices is improved nutritional content, but the evidence and context is not clear. A scoping review of recent literature (Web of Science, 2000–2021) was carried out to assess the evidence that RA approaches improve crop micronutrient quality. Papers included covered combinations of agronomic approaches that could be defined as Regenerative: “Organic Inputs” including composts and manures, cover crops, crop rotations, crop residues and biochars; “Reduced Tillage”, “Intercropping”, “Biostimulants” e.g. arbuscular mycorrhizal fungi; plant growth promoting bacteria, and “Irrigation”, typically deficit-irrigation and alternate wetting and drying. The crop types reviewed were predetermined covering common sources of food and included: Tomato (Solanum lycopersicum L.), Wheat (Triticum aestivum L.), Rice (Oryza sativa L.), Maize (Zea mays L.), Pulses (Fabaceae), Alliums (Allium spp.), and “other” crop types (30 types). This scoping review supports a potential role for RA approaches in increasing the concentrations of micronutrients in the edible portions of several crop types under specific practices. Eighty-seven percent of studies included on rice under increased “organic inputs” showed significant increases in zinc (Zn) content. Vitamin C was the most assessed nutrient in tomatoes and increased significantly in just under half of the studies implementing increased “organic inputs” with no significant change in the other half, suggesting context is important, and practice alone does not drive changes. Overall, 76% of studies on deficit irrigation in tomatoes resulted in significantly higher vitamin C levels. Overall, the magnitude and reproducibility of the effects of RA practices on most crop nutritional profiles were difficult to assess due to the diversity of RA approaches, geographical conditions, and the limited number of studies for most crops in each of these categories. Future research with appropriate designs, improved on-farm surveillance and nutritional diagnostics are needed for better understanding the potential role of RA in improving the quality of food, human nutrition, and health.